At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Discover reliable solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To determine which expression is equivalent to [tex]\(\left(\frac{1}{16}\right)^{-4}\)[/tex], let's analyze each option step by step.
First, we compute [tex]\(\left(\frac{1}{16}\right)^{-4}\)[/tex]:
Recall the exponent rule for negative exponents: [tex]\(a^{-b} = \frac{1}{a^b}\)[/tex].
Applying this rule:
[tex]\[ \left(\frac{1}{16}\right)^{-4} = \left(\frac{16}{1}\right)^4 = 16^4 \][/tex]
Now we must check which option matches [tex]\(16^4\)[/tex]. Let's evaluate each option:
1. Option 1: [tex]\(-(16^4)\)[/tex]
- Calculating [tex]\( -(16^4) \)[/tex]:
[tex]\[ -(16^4) = -65536 \][/tex]
2. Option 2: [tex]\(16^4\)[/tex]
- Calculating [tex]\( 16^4 \)[/tex]:
[tex]\[ 16^4 = 65536 \][/tex]
3. Option 3: [tex]\(\sqrt[4]{\frac{1}{16}}\)[/tex]
- Calculating [tex]\(\sqrt[4]{\frac{1}{16}}\)[/tex]:
[tex]\[ \sqrt[4]{\frac{1}{16}} = \left(\frac{1}{16}\right)^{\frac{1}{4}} = \frac{1}{16^{\frac{1}{4}}} = \frac{1}{2} \][/tex]
4. Option 4: [tex]\(-\left(\frac{1}{16}\right)^{-4}\)[/tex]
- Calculating [tex]\(-\left(\frac{1}{16}\right)^{-4}\)[/tex]:
[tex]\[ -\left(\frac{1}{16}\right)^{-4} = -16^4 = -65536 \][/tex]
Comparing these results with [tex]\(\left(\frac{1}{16}\right)^{-4}\)[/tex]:
- [tex]\(\left(\frac{1}{16}\right)^{-4} = 65536\)[/tex]
- Option 1: [tex]\(-(16^4) = -65536\)[/tex] (not equivalent)
- Option 2: [tex]\(16^4 = 65536\)[/tex] (equivalent)
- Option 3: [tex]\(\sqrt[4]{\frac{1}{16}} = 0.5\)[/tex] (not equivalent)
- Option 4: [tex]\(-\left(\frac{1}{16}\right)^{-4} = -65536\)[/tex] (not equivalent)
Therefore, the expression that is equivalent to [tex]\(\left(\frac{1}{16}\right)^{-4}\)[/tex] is [tex]\(16^4\)[/tex].
So, the correct answer is:
[tex]\[ \boxed{16^4} \][/tex]
First, we compute [tex]\(\left(\frac{1}{16}\right)^{-4}\)[/tex]:
Recall the exponent rule for negative exponents: [tex]\(a^{-b} = \frac{1}{a^b}\)[/tex].
Applying this rule:
[tex]\[ \left(\frac{1}{16}\right)^{-4} = \left(\frac{16}{1}\right)^4 = 16^4 \][/tex]
Now we must check which option matches [tex]\(16^4\)[/tex]. Let's evaluate each option:
1. Option 1: [tex]\(-(16^4)\)[/tex]
- Calculating [tex]\( -(16^4) \)[/tex]:
[tex]\[ -(16^4) = -65536 \][/tex]
2. Option 2: [tex]\(16^4\)[/tex]
- Calculating [tex]\( 16^4 \)[/tex]:
[tex]\[ 16^4 = 65536 \][/tex]
3. Option 3: [tex]\(\sqrt[4]{\frac{1}{16}}\)[/tex]
- Calculating [tex]\(\sqrt[4]{\frac{1}{16}}\)[/tex]:
[tex]\[ \sqrt[4]{\frac{1}{16}} = \left(\frac{1}{16}\right)^{\frac{1}{4}} = \frac{1}{16^{\frac{1}{4}}} = \frac{1}{2} \][/tex]
4. Option 4: [tex]\(-\left(\frac{1}{16}\right)^{-4}\)[/tex]
- Calculating [tex]\(-\left(\frac{1}{16}\right)^{-4}\)[/tex]:
[tex]\[ -\left(\frac{1}{16}\right)^{-4} = -16^4 = -65536 \][/tex]
Comparing these results with [tex]\(\left(\frac{1}{16}\right)^{-4}\)[/tex]:
- [tex]\(\left(\frac{1}{16}\right)^{-4} = 65536\)[/tex]
- Option 1: [tex]\(-(16^4) = -65536\)[/tex] (not equivalent)
- Option 2: [tex]\(16^4 = 65536\)[/tex] (equivalent)
- Option 3: [tex]\(\sqrt[4]{\frac{1}{16}} = 0.5\)[/tex] (not equivalent)
- Option 4: [tex]\(-\left(\frac{1}{16}\right)^{-4} = -65536\)[/tex] (not equivalent)
Therefore, the expression that is equivalent to [tex]\(\left(\frac{1}{16}\right)^{-4}\)[/tex] is [tex]\(16^4\)[/tex].
So, the correct answer is:
[tex]\[ \boxed{16^4} \][/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.